A care counselling model for HIV reactive patients in rural Malawi--Part II - Sliep, Y; Poggenpoel, M; Gmeiner, A (Curationis (Pretoria), 2001)
The purpose of the research conducted was to explore and describe HIV patients experience of their illness within the context of rural Malawi and, based on the results of the study, to describe a model for counselling HIV reactive patients in rural Malawi which would meet both the internal and external needs of the patient. Nursing for the Whole Person Theory, as well as symbolic interactionism and the research model of Botes, were used as paradigm, as the researcher believes a person is fundamentally a historical social being who can only be understood in a specific cultural context of space and time. The research was also conducted within a counselling context and different disciplines were integrated in the study. The research method followed two phases each addressing a different objective. Firstly, exploration and description of the HIV reactive individual's experience of illness, compilation of a demographic profile of the patients in the study and a description of their identified needs as well as possible resources, exploration and description of the primary care givers' experience of HIV reactive patients and the exploration and description of the viewpoint of counsellors in terms of counselling HIV reactive patients. In the first phase of the study in-depth phenomenological interviews were conducted with identified groups. Focus interviews were conducted with a hundred AIDS patients to identify the needs and resources of the patients and to compile a demographic profile. Focus groups discussions were conducted with counsellors for more complete comprehension. Data-analysis and literature control was undertaken. In the second phase of the study theory generation was used in order to develop a counselling model for AIDS patients and guidelines for implementing the model were generated. Based on the results of the analysis the major concept enable was identified as the essence of a model for counselling AIDS patients in rural Malawi. The visual model developed described a process of enablement with the counsellor as negotiator and the patient as a narrator in which the patient, family and community are encouraged to participate actively. By utilising the deductive reasoning strategy, relationship statements were inferred from the model. Guidelines were described for all three phases of the model, namely pretest counselling, post-test counselling and community care, in terms of objectives, strategies and activities. The value of this research was embodied in addressing a very real and urgent need in Malawi and proposing a solution with practical guidelines.